Resilience-driven restoration model for interdependent infrastructure networks - Almoghathawi, Yasser; Barker, Kash; Albert, Laura A. (Reliability engineering & system safety, 2019)
–A multi-objective optimization model is developed to restore disrupted components of interdependent infrastructure networks.–Objectives of resilience and cost are balanced.–The model is illustrated with generated networks representing power and water networks. Critical infrastructure networks such as electric power, water distribution, natural gas, transportation and telecommunications are the backbone of modern societies as they provide them with the services that are essential for their continuous functioning. However, these infrastructure networks are not isolated from each other but instead, most of them rely on one another to be functional. Hence, they are highly vulnerable to any disruptive event (e.g., components deteriorating, terrorist attacks, or natural disasters) which makes their restoration more challenging task for decision makers. In this paper, we study the restoration problem of a system of interdependent infrastructure networks following a disruption event considering different disruptions scenarios. We propose a resilience-driven multi-objective restoration model using mixed-integer programming that aims to maximize the resilience of the system of interdependent infrastructure networks while minimizing the total cost associated with the restoration process. The restoration model considers the availability of limited time and resources and provides a prioritized list of components, nodes or links, to be restored along with assigning and scheduling them to the available work crews. The proposed model is illustrated through a generated system of interdependent power-water networks, however it is applicable to any physically interdependent networks.